A planar beam splitter for millimetre and sub-millimetre heterodyne mixer array - Tan, BK; Yassin, G (Institute of Electrical and Electronics Engineers, 2017)
We present the design of a four-port planar circuit beam splitter comprising a microstrip and a coplanar waveguide (CPW) crossing each other. The CPW is fabricated in the ground plane (bottom layer) and the microstrip is deposited on top of the dielectric layer. A small section of the microstrip line is bent and aligned parallel to the central conductor of the bottom CPW, allowing the level of power coupling to be easily controlled by changing the length of the aligned section. The simple layout of the planar beam splitter makes it easy to fabricate in a wide frequency range from microwave to submillimetre (sub-mm) wavelengths. In this paper, we describe in details the electromagnetic design of the planar beam splitter and its predicted performances in the frequency range of 600– 700 GHz. We discuss the potential usage of the planar beam splitter as a replacement to the free-space beam splitter in receivers, in particular those using superconductor-insulatorsuperconductor (SIS) mixer arrays. To investigate the integrity of our design in a controlled way we scaled the design to operate in the Ku-band and measured the performance of several prototypes experimentally. Our tests showed good agreement between the measured performance and simulations.